Respuesta inmune sistémica y mucosal contra Neisseria meningitidis B inducida por estrategia de vacunación simultánea mucosal y parental - González E; Romeu B; del Campo J; Acevedo R; Lastre M; Zayas C; Cuello M; Cabrera O; Balboa J; Nuñez N; Valdez Y; Fariñas M; et al. (VacciMonitor, 2009)
mmunization is one of the most successful and cost-effective health interventions ever. Immunization have been helping to reduce child mortality, improving maternal health and combating infectious diseases. In spite of its, undisputed past success and promising future, however, immunization remains an unfinished agenda because of them inadequate coverage. Several factors have been largely responsible of a difficulty to attain immunization coverage and have been recognized as a problems of current vaccines, such as: the number of dose, excessive use of parenteral route, a small number of adjuvants approve for use in human, higher reactogenicity and unavailability against intracellular pathogens, infected or altered cells and scanty feasibility to combined more than one antigen in the same formulation. For bacterial meningitis WHO estimates that 1.2 million cases occur annually and Neisseria meningitidis is the etiological agent in more than 40% of these cases although some meningococcal vaccines are available. To bear in mind these principals problems, a novel protocol for vaccination against N. meningitidis called Single Time Vaccination Strategy (SinTimVaS) is proposed. Using female BALB/c mice, we induce systemic and mucosal immune responses against N. meningitidis with only one parenteral and one mucosal dose at the same time, employing the Finlay Adjuvants derivate from N. meningitidis, AFPL1 and AFCo1, respectively. In conclusion, SinTimVaS could increase the vaccination coverage and reduce the time-cost of vaccine campaigns, adding the possibility to increase the herd immunity by mucosal specific response induction.